Real Time Monitoring with Indigenous Peoples: Technical, Social and Political Challenges, and Lessons from Brazil. (21st March 2013) - Shankland, Alex; Toledo, Maria Elvira; Barbosa, Adriana; Bittencourt, Maria Ferreira
Abstract The government of Brazil has introduced two health and nutrition monitoring systems (the Indigenous Health Care Information System (SIASI) and the Food and Nutrition Surveillance System for Indigenous People (SISVAN‐I) as part of reforms to health care and social protection services for indigenous peoples, who have the worst health status of any population group in the country. This article covers the origins and development of these systems and examines their functioning in one local health district, which serves the Xavante people. It assesses the systems' performance in relation to the aspects established in the case study terms of reference: quality of information, inclusivity, relevance to potential users, costs and sustainability. A number of key issues are identified. Some are intrinsic to the technical, cultural and political challenges of working with indigenous peoples, while others reflect problems with the implementation of responses to these challenges at different levels in Brazil.